Handbook on the economics of copyright a guide for students and teachers - aWatt, Richard 1963- (Edward Elgar Publishing, 2014)
This handbook provides comprehensive coverage of the economics of copyright, and provides a useful teaching and learning resource. The chapters deal with the basic underlying principles, the main contributing literature and, in some cases, new extensions to the field. -- Source other than the Library of Congress.